Analysis of Maritime Potential Development in Improving Fishermen's Welfare: Islamic Economic Review (Case Study of Belawan Fishermen) - Aqli Nadzhari Rambe; Muhammad Syukri Albani Nasution; Muhammad Lathief Ilhamy Nasution (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2026)
The welfare of traditional fishermen remains a persistent challenge in coastal regions despite abundant maritime potential, particularly in Belawan, Indonesia. Previous studies have largely emphasized economic and technical aspects of fisheries development, with limited integration of Islamic economic principles in sustainable welfare strategies. This study aims to examine maritime development strategies to improve fishermen’s welfare through an Islamic economic perspective.This research employs a qualitative field approach with a case study design conducted in Belawan Bahagia and Belawan Bahari sub-districts. Informants were purposively selected from traditional fishermen, community leaders, and relevant stakeholders. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the marketing mix (4Ps) and SWOT framework, supported by IFAS and EFAS matrices.The findings indicate strong internal potential, including high-quality, preservative-free seafood and solid social networks. However, challenges such as limited cold storage, low digital literacy, and dependence on middlemen persist. With an IFAS score of 3.06 and EFAS score of 2.50, fishermen are positioned in an aggressive growth strategy, emphasizing diversification, sharia-based cooperatives, and digital expansion, aligning with maqasid al-shariah values.